Analyzing the diversity and inclusivity of Philippine exports to the European union under the GSP+ - Julia, Bryann Jonsson R. (2022)
This study assesses the diversity and inclusivity of Philippine export activities
to the European Union (EU) amid the country’s status as a beneficiary of the
Generalised Scheme of Preferences Plus (GSP+). The GSP+ is a trade agreement
that removes EU tariffs in exchange for the compliance of developing countries
with international conventions, such as on human and labor rights, environmental
protection, and good governance. To assess the economic incentives of GSP+
and determine how and why its outcomes evolved in such a manner, this paper
gathered official statistics and documents as well as open-ended questionnaires
and email correspondence with experts and key informants from the government
sector. The study argues that factors beyond the scope of the GSP+, including the
country’s reliance on transnational migration, trade and investment liberalization,
and private consumption, and challenges pertaining to the capacities of exporters,
local supply chains and infrastructures, public institutions, and income and
political inequalities, can be attributed to the peculiar political economy of the
Philippines, which scholars touted as an antidevelopmental state.
Keywords: Philippine - economic relations - European Union